Application of remotely sensed image of SPOT5 to land use change survey - FENG Xiu-li; WANG Ke; LOU Li-ming (浙江大学学报. 农业与生命科学版, 2005)
This paper discussed the image fusion methods of SPOT5 multi-spectral bands and SPOT5 panchromatic band for improving land use change survey accuracy. HIS (Hue, Intensity, Saturation) transform and Principal Components Analyse transform were applied to the test data, then visual interpretation and man-computer interactive interpretation methods were used to classify the fusion image. The accuracy of different fusion methods was compared. The results indicated that it was better to apply different fusion methods to SPOT5 image integratedly to carry on land use change survey and output result map at 1∶10000 scale.